Beta cell function and insulin sensitivity in obese youth with maturity onset diabetes of youth mutations vs type 2 diabetes in TODAY: Longitudinal observations and glycemic failure. Issue 4 (3rd March 2020) - Arslanian, Silva; El ghormli, Laure; Haymond, Morey H.; Chan, Christine L.; Chernausek, Steven D.; Gandica, Rachelle G.; Gubitosi‐Klug, Rose; Levitsky, Lynne L.; Siska, Maggie; Willi, Steven M.
Abstract: Objective: In treatment options for type 2 diabetes in adolescents and youth (TODAY), 4.5% of obese youth clinically diagnosed with type 2 diabetes (T2D) had genetic variants consistent with maturity onset diabetes of youth (MODY) diagnosis. The course of IS and β‐cell function in obese youth with MODY remains unknown. In this secondary analysis, we examined IS and β‐cell function in MODY vs. non‐MODY obese youth at randomization and over time. Methods: Genetic data in TODAY included 426 non‐MODY (T2D) and 22 MODY youth (7 glucokinase MODY mutation positive [GCK‐MODY], 12 hepatocyte nuclear factor MODY mutation positive [HNF‐MODY], 2 Insulin gene mutation [insulin (INS)‐MODY], and 1 Kruppel‐like factor 11 [KLF11‐MODY]). Oral glucose tolerance test (OGTT)‐derived IS, C‐peptide index, and β‐cell function relative to IS oral disposition index (oDI) was measured at randomization, and over 24 months in addition to total and high‐molecular‐weight adiponectin (HMWA). Results: At randomization, IS, total adiponectin, and HMWA were significantly higher in the two MODY groups than in non‐MODY. β‐cell function measured by C‐peptide oDI was 3‐fold higher in GCK‐MODY than in HNF‐MODY and 1.5‐fold higher than non‐MODY ( P for both <.05). Glycemic failure rate was 75.0% in HNF‐MODY, 46.9% in non‐MODY, and zero in GCK‐MODY youth. While the changes in IS and oDI were not different among the three groups in the first 6 months, IS improved from 6 to 24 months in HNF‐MODY vs GCK‐MODY youth. Conclusions: In TODAY, β‐cell function at randomization was worse in obese HNF‐MODY youth compared with GCK‐MODY youth, while insulin sensitivity was worse in non‐MODY compared with the other two MODY groups. Over time, IS showed the greatest improvement in HNF‐MODY youth. This raises the possibility that TODAY therapeutic modalities of insulin sensitization in these obese HNF‐MODY youth may have played a beneficial role.